CLINICAL AND PARACLINICAL CHARACTERISTICS AND CORONARY ARTERY LESIONS IN PATIENTS WITH PERCUTANOUS CORONARY ANGIOPGRAPHY AND INTERVENTION AT HUNG VUONG GIA LAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical, paraclinical characteristics and coronary artery lesions in patients undergoing coronary angiography and intervention at Hung Vuong Gia Lai Hospital.Methods: A cross-sectional descriptive study was conducted on 95 patients admitted for coronary angiography and/or percutaneous coronary intervention from June 2024 to May 2025. Clinical features, paraclinical findings, and coronary lesions were analyzed using descriptive statistics.Results: Most patients were male and aged over 55 years. Hypertension was the most common cardiovascular risk factor. Chest pain was the predominant presenting symptom, and most patients were admitted with acute coronary syndromes. Common paraclinical abnormalities included uncontrolled LDL-C levels, elevated troponin T, and typical electrocardiographic changes. Severe coronary lesions were mainly located in major vessels, particularly the left anterior descending and right coronary arteries. Most patients had 1-2 significant lesions.Conclusion: This study provides descriptive data on clinical, paraclinical, and angiographic characteristics at a provincial hospital.
Keywords: Coronary artery disease, coronary angiography, percutaneous coronary intervention, coronary artery lesions.